The Influence of the Use of Polya's Heuristic Strategies on Students' Mathematical Problem Solving: A Meta Analysis - Wahab A, Abdul; Dasari, Dadan; Juandi, Dadang; Syaiful (Journal of Mathematics Learning Innovation, 2024)
Mathematics education in Indonesia faces significant challenges, as reflected in the low performance of students in various international assessments. Traditional teaching methods, which are less interactive, are considered one of the key factors contributing to students' low problem-solving abilities in mathematics. This meta-analysis aims to evaluate the impact of Polya's heuristic model on students' mathematical learning outcomes and determine the extent to which this strategy can enhance students' learning abilities compared to conventional teaching methods. The study employs a meta-analytic approach, integrating data from 15 primary studies conducted between 2014 and 2023, and uses statistical analysis to calculate the average effect size of the implementation of Polya's heuristic model in mathematics education. The findings reveal a significant improvement in students' mathematical learning outcomes using Polya's heuristic model, with an average effect size of 1.13, categorized as "very high." The study suggests that the application of Polya's heuristic model is significantly more effective in enhancing students' mathematical learning outcomes than conventional teaching methods. The practical implication is that educators and policymakers in Indonesia could consider adopting this strategy in curricula and teacher training programs to improve the quality of mathematics education.